THE INTERIOR OF THINGS: THE ORIGAMI OF BEING. - Bryant, Levi R. (Arts & Cultural Studies Review / Przegląd Kulturoznawczy, 2016)
In The Interior of Things: The Origami of Being Bryant develops a critique of object-oriented philosophy and its thesis that objects are withdrawn from one another or never touch. Arguing that such a position is ultimately incoherent, Bryant instead proposes an ontology of folds and folding in which the minimal unit of existence is conceived as the fold between thing and field such that things interiorize the field out of which they emerge. In this way Bryant is able to account for relationality among beings while also maintaining their irreducible singularity resulting from the unique way in which things pleat their world. What emerges is a profoundly ecological conception of existence in which beings are perpetually pleating their world.